Prevalence and burden of anhedonia among patients with major depressive disorder in South Korea: A cross-sectional, observational study - Bolam Lee; YoungDoe Kim; HeeKyung Eum; Ja Seo Koo; Keira Herr; Lawrence Vandervoort; Jung Goo Lee (PLoS ONE, 2025)
Background Anhedonia (ANH), a key symptom of major depressive disorder (MDD), has a substantial societal and economic burden. In South Korea, while MDD is prevalent, the evidence regarding anhedonia remains scarce. This study investigated the prevalence and impact of anhedonia in patients with MDD in South Korea, including patient and physician perceived goals and satisfaction with MDD treatment. Methods This cross-sectional study (April-May 2023) included two surveys, one specific to patients (aged ≥18 years) with self-reported physician diagnosis of MDD and 9-item Patient Health Questionnaire (PHQ-9) score≥10, and another to physicians treating MDD. The MDD group was classified as MDD-ANH (Snaith-Hamilton Pleasure Scale [SHAPS] score≥3) and MDD non-ANH (SHAPS score≤2). Multiple regression models were employed to evaluate the effect of anhedonia on health-related quality of life (HRQoL), work productivity and activity impairment, and healthcare resource utilization (HCRU). Results Of 4496 participants, the age- and gender-weighted prevalence of MDD was 9.9%, of which 61.5% self-reported anhedonia. Patients with MDD-ANH (vs. MDD non-ANH) had longer duration of depression since diagnosis and lower prior and current antidepressants use (all, p < 0.05). Similarly, patients with MDD-ANH (vs. MDD non-ANH) demonstrated lower HRQoL, and increased HCRU (all, p < 0.05). Patients with MDD-ANH prioritized treatment goal of improved sleep quality, while physicians prioritized avoiding suicidal thoughts. Similarly, patients with MDD-ANH had highest level of satisfaction with controlled depressed mood and physicians with improved sleep quality. Both groups reported lowest level of satisfaction with regaining interest in hobbies, regaining self-esteem, and improving sexual satisfaction. Conclusions This is the first study in South Korea to estimate the prevalence of anhedonia in patients with MDD, highlighting the disease burden and unmet medical needs. Furthermore, disparities observed between patients and physicians in the goals and expectations of MDD treatment underscore the need to monitor anhedonia for treatment optimization.